Interlacing Planning and Degrowth Scholarship. A Manifesto for an Interdisciplinary Alliance. - Ferreira, António; Schönfeld, Kim Carlotta von (Taylor & Francis, 2020)
Due to the persistent pursuit of economic growth, contemporary Western societies are inducing an increasingly deep economic, environmental, and social crisis. Planning has significantly contributed to the pursuit of growth and, as a consequence, urban areas have experienced a number of problematic transformations. The establishment of an alliance between planning and degrowth scholarship could contribute to address these issues. To clarify the potential outlines of this alliance, some of the key principles of both progrowth and degrowth scholarship are critically reviewed. Following this, insights are offered in particular for planners and planning academics wanting to promote the formation of this interdisciplinary alliance.
Keywords: Planungstheorie; Wirtschaftswachstum; Wachstumsgrenze; Krisensituation; Planerausbildung; Interdisziplinarität; Curriculum; Postwachstum